2022
DOI: 10.3390/v14050867
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zero-Valent Iron Nanoparticles (nZVI) on Bacteriophages

Abstract: Bacteriophages are viruses that attack and usually kill bacteria. Their appearance in the industrial facilities using bacteria to produce active compounds (e.g., drugs, food, cosmetics, etc.) causes considerable financial losses. Instances of bacteriophage resistance towards disinfectants and decontamination procedures (such as thermal inactivation and photocatalysis) have been reported. There is a pressing need to explore new ways of phage inactivation that are environmentally neutral, inexpensive, and more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…The inactivating effect of 1 mg/ml of Fe 3+ ions on various unrelated phages was previously noticed by Raza et al (2022). Similar, but weaker activity of 5 mM Cu 2+ ions, was observed against dsDNA phages by Li and Dennehy (2011).…”
Section: Phage Stabilitysupporting
confidence: 79%
“…The inactivating effect of 1 mg/ml of Fe 3+ ions on various unrelated phages was previously noticed by Raza et al (2022). Similar, but weaker activity of 5 mM Cu 2+ ions, was observed against dsDNA phages by Li and Dennehy (2011).…”
Section: Phage Stabilitysupporting
confidence: 79%
“…The most investigated NPs are based on metals, e.g., silver, copper oxide, and titanium dioxide. Nanoparticles might act via three distinct mechanisms: (i) adsorbing on the surface and destabilizing the protein structure, (ii) releasing ions, and (iii) generating reactive oxygen species [ 150 ]. The same mechanisms are also valid while considering the antibacterial properties of nanoparticles.…”
Section: Future Outlook: New Antiphagentsmentioning
confidence: 99%
“…It was also observed that the higher the concentration of iron ions, the more phages are inactivated [ 157 ]. Another interesting example was the zero-valent iron particles [ 150 ].…”
Section: Future Outlook: New Antiphagentsmentioning
confidence: 99%